The Influence of Marketing Innovation on Increasing MSME Sales - Mustari Mustari; Nur Arisah (Citakonsultindo, 2025)
The purpose of this research is to ascertain whether or not marketing innovation contributes to the expansion of sales at SMEs. The author used a descriptive methodology combined with qualitative data analysis to conduct her study, with in-depth interviews providing the primary source material for her findings. Micro, small, and medium sized company student entrepreneurs made up the study's population, from which 8 respondents were chosen for the sample. Descriptive analysis using a qualitative approach is used to analyze the data, specifically to describe the study outcomes in their raw form with the editing and coding processes that led to those results. The study's findings suggest that MSMEs might boost their revenue via creative marketing strategies.